2017
DOI: 10.1021/acs.accounts.6b00321
|View full text |Cite
|
Sign up to set email alerts
|

Entropy and Enzyme Catalysis

Abstract: The role played by entropy for the enormous rate enhancement achieved by enzymes has been debated for many decades. There are, for example, several confirmed cases where the activation free energy is reduced by around 10 kcal/mol due to entropic effects, corresponding to a rate enhancement of ∼10 compared to the uncatalyzed reaction. However, despite substantial efforts from both the experimental and theoretical side, no real consensus has been reached regarding the origin of such large entropic contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 40 publications
2
101
0
Order By: Relevance
“…Consideration of the enthalpic and entropic components of the binding free energy has recently been suggested to be an important metric to guide fragment optimization 8 . In addition to improved predictions of relative affinities, MD/FEP calculations make it possible to characterize the driving forces behind a change in free energy, which has previously been applied successfully to study ion hydration 28 and enzyme catalysis 34 . In this work, we used the same approach to investigate the large differences in binding observed for two compound pairs from the series of adenine-based ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of the enthalpic and entropic components of the binding free energy has recently been suggested to be an important metric to guide fragment optimization 8 . In addition to improved predictions of relative affinities, MD/FEP calculations make it possible to characterize the driving forces behind a change in free energy, which has previously been applied successfully to study ion hydration 28 and enzyme catalysis 34 . In this work, we used the same approach to investigate the large differences in binding observed for two compound pairs from the series of adenine-based ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is entropy driven, which in turn impacts the p K values (Eq (1)). Although close proximity and orientation reduces the entropy of reactions, a full understanding of the complex nature of the entropic effect will require an extensive study of the active site environment and its surroundings [55]. Similarly in this study, we propose that the enhanced adsorption strength of Cl − anions in the presence of competing phthalate anions may be due to the enhanced reactivity of the protonated surface sites by the phthalate anions.…”
Section: Resultsmentioning
confidence: 69%
“…Two recently published approaches intended to develop a hypothesis that the transition state in the solid-state chemical reactions is conditioned by the "softness" of the surrounding molecular arrangement. As we have mentioned in the Introduction, the first of them appears in the research of the activation enthalpy-entropy adaptations in the enzyme catalyzed reactions, [20] and the second demonstrated that a sort of the transition liquid phase appears during the solid-solid transformation. [12] By measuring and analyzing the activation parameters of the solid-state reactions of aromatic C-nitroso compounds we wish to contribute in deepening this discussion.…”
Section: Resultsmentioning
confidence: 99%
“…As it follows from the recent literature, influence of the softness of condensed phase on the organic reactivity is not limited to the reactions in the crystalline solids only. The relationship between the activation entropy term (‐ T Δ ≠ S °) in the regulation of the enzyme catalysed reaction rates that occur in various mutants, is also interpreted by the different softness of the enzyme reaction cavity . Evolutionary “cold adaptation” of organisms is based upon the enzyme mutation, which does not basically change the topotactical arrangement in the active site, but rather the outer polypeptide structure, which modifies the rigidity of the reactive cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation